Constituição docente do enfermeiro: o estado da arte das produções brasileiras - Agnelli, Jeferson Cesar Moretti (2017)
The action of teaching is strongly rooted in a teacher's training. Assuming that teaching is one of the possible fields of action of the nurse, and that it requires specific training considering that it constitutes a field of science, the present research aims to understand the Nursing Teacher Constitution based on Brazilian productions. Bringing with it several elements of personal experience that emerges from the condition of the researcher as a nurse and a nursing teacher, intentionally responding the research question: is it enough to be a nurse to be a nursing teacher? Is there a relation of proximity from the nurse with the teaching and pedagogical knowledge during the professional practice of teaching? Do nurses have eligible criteria for teacher training during nursing graduation or in teacher training courses? In this context, we chose to conduct the type of the research from the state of art, having Romanowski (2006) as a theoretical reference. We made a search for Brazilian productions in the Bank of Theses and Dissertations and Portal of Periodicals from CAPES. We identified 50 productions that enabled us to discuss the Nursing Teacher Constitution from the training for professional practice in Technical and Higher Education and from the teaching practice of the Professor Nurse. We draw from this study that the Nursing Teacher Constitution from the training is given through the degree in nursing or through graduate programs. The constitution from the teaching practice is given through the experiential knowledge and initial training for teaching. We understand, however, that the nurses' constitution is multifaceted, taking as possible paths the pedagogical training programs as both (initial and continued) as well as the path of the teaching practice itself.